Influência do método de preparação de eletrocatalisadores PtRu/C sobre a atividade catalítica frente à reação de oxidação de etanol em meio ácido - GOMES, Walber dos Santos (2016)
In this work the influence of variations in the borohydrate reduction method on the properties of PtRu/C electrocatalysts was investigated. The electrocatalysts were prepared using 1:1 ; 2:1; 5:1; 50:1 and 250:1 molar ratios of NaBH4 to metals. The reduction was also performed by dripping or by fast addition of the solution. The results showed that PtRu nanoparticles obtained by fast addition had the smallest crystallite sizes. It was also noted that the catalytic activity increased as the borohydrate:metal molar ratio increased. The PtRu/C electrocatalyst (50:1) obtained by fast addition presented the best catalytic activity for ethanol electro-oxidation.